Magnetic properties of hematite in lava flows from Iceland: Response to hydrothermal alteration (Dataset) ... - Beske-Diehl, Suzanne; Huiling Li (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Magnetic properties of hematite in lava flows from Iceland: Response to hydrothermal alteration ...